Long-term dietary supplementation with saury oil attenuates metabolic abnormalities in mice fed a high-fat diet: combined beneficial effect of omega-3 fatty acids and long-chain monounsaturated fatty acids. Issue 1 (December 2015) - Yang, Zhi-Hong; Inoue, Seika; Taniguchi, Yasuko; Miyahara, Hiroko; Iwasaki, Yusuke; Takeo, Jiro; Sakaue, Hiroshi; Nakaya, Yutaka
Abstract Background Pacific saury is a common dietary component in East Asia. Saury oil contains considerable levels of n-3 unsaturated fatty acids (PUFA) and long-chain monounsaturated fatty acids (LCMUFA) with aliphatic tails longer than 18 carbons. In our previous study, consumption of saury oil for 4 to 6 wk improved insulin sensitivity and the plasma lipid profile in mice. However, the long-term effects of saury oil on metabolic syndrome (MetS) risk factors remain to be demonstrated. In the current study, we examined the long-term effects of saury oil on mice fed a high-fat diet, and compared the effect of n-3 PUFA EPA and LCMUFA on MetS risk factor in diet-induced obese mice. Methods and Results In Experiment 1, male C57BL/6 J mice were fed either a 32 % lard diet (control) or a diet containing 22 % lard plus 10 % saury oil (saury oil group) for 18 weeks. Although no differences were found in body weight and energy expenditure between the control and saury oil groups, the saury oil diet decreased plasma insulin, non–HDL cholesterol, hepatic steatosis, and adipocyte size, and altered levels of mRNA transcribed from genes involved in insulin signaling and inflammation in adipose tissue. Organ and plasma fatty acid profile analysis revealed that consumption of saury oil increased n-3 PUFA and LCMUFA (especially n-11 LCMUFA) levels in multiple organs, and decreased the fatty acid desaturation index (C16:1/C16:0; C18:1/C18:0) in liver and adipose tissue. In Experiment 2, male C57BL/6 J mice were fed a 32 % lard diet (control), a diet containing 28 % lard plus 4 % EPA (EPA group), or a diet containing 20 % lard plus 12 % LCMUFA concentrate (LCMUFA group) for 8 weeks. EPA or LCMUFA intake increased organ levels of EPA and LCMUFA, respectively. Consumption of EPA reduced plasma lipid levels and hepatic lipid deposition, and decreased the fatty acid desaturation index in liver and adipose tissue. Consumption of LCMUFA decreased plasma non–HDL cholesterol, improved hyperinsulinemia, and decreased the fatty acid desaturation index in adipose tissue. EPA accumulated mainly in liver, and LCMUFA (especially n-11 LCMUFA) accumulated mainly in white adipose tissue, suggesting their possible individual biological effects for improving MetS. Conclusion Our results suggest that saury oil-mediated improvement of metabolic syndrome in diet-induced obese mice may possibly be due to a combined effect of n-3 PUFA and LCMUFA.